Promoting Social Cohesion through Education : Case Studies and Tools for Using Textbooks and Curricula - Roberts-Schweitzer, Eluned (Washington, DC: World Bank, 2012)
Since 2003, the Civic Engagement, Empowerment, and Respect for Diversity (CEERD) program of the World Bank Institute has included a program on Education and Respect for Diversity. The program consists of a series of initiatives to promote tolerance and respect for diversity through curriculum and textbook reform and pre- and in-service teacher training. To date it has focused on ways in which Bank-financed programs can help education systems to address the needs of all students and to promote social cohesion. Activities have included information dissemination, through workshops and papers, as well as financing for pilot programs in Colombia, the Lao People's Democratic Republic, Nigeria, Romania, and Sri Lanka. These pilots are designed to put in place strategies that can be scaled up either in the pilot country or in other programs.